Open-Circuit Fault Detection Technique for Fault-Tolerant Bridgeless Boost Rectifier - K Abdul Razak, R; S Muhammad, K; Baharom, R; M I Mamat, A (International Journal of Engineering and Technology, 2018)
Unexpected failure in one of the switches in a converter will lessen the performance of a system and may even prompt to a system failure. Therefore, to reduce the failure rate and to prevent unscheduled shutdown, a real-time fault detection is necessary. In this paper, a new technique to identify the exact location of the faulty switch based on single-phase bridgeless boost converter is proposed. The faulty switch is detected by analyzing the boost inductor current, switching mode and cycle of the input power supply. The information of the faulty switch will be used to redirect the current to any available path. Therefore, an uninterruptable and reliable power supply could be developed. The analysis of the proposed fault detection scheme is done by using PSIM simulation software.Â Â